TRANSFORMATIONAL LEADERSHIP OF MADRASAH PRINCIPALS IN DEVELOPING STUDENTS’ RELIGIOUS CHARACTER - Halimatus Sa’diyyah; Subaidi Subaidi (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2026)
This study uses transformational leadership as a theoretical lens to understand the practices of school principals, not just as a label. is motivated by the importance of developing students' religious character amidst the challenges of the digital era, especially in rural madrasas facing limited resources and minimal leadership training. MI Tarbiyatul Athfal in Gunungwungkal District, Pati Regency, became the locus of study because it was deemed successful in implementing religious values habituation despite limited conditions. The research objectives were to describe the role and leadership strategies of the principal, analyze supporting and inhibiting factors, and reveal their impact on the formation of students' religious character. The study used library research methods with a qualitative descriptive-analytical approach and content analysis techniques on internal madrasah documents and the latest scientific literature (2015–2025). The results show that the principal plays a role as a moral agent and spiritual leader through four dimensions: formulation of a religious vision, exemplary morals and worship, management of value habituation (Dhuha prayer, tadarus, daily etiquette), and collaboration with teachers and parents. The main strategy is sustainable habituation integrated into the school culture. Supporting factors include the principal's religious commitment and local environmental support, while the main obstacles are limited human resources, minimal training, and negative digital influences. This study proposes an adaptive, contextual model of religious leadership in semi-rural areas.